From Courtesan to Wŏn Buddhist Teacher: The Life of Yi Ch’ŏngch’un - Grace J. Song (Religions, 2023)
This study examines the life of Yi Ch’ŏngch’un 李靑春 (1886–1955), one of the first female disciples of Wŏn Buddhism, a 20th-century Korean religious movement. Her story shows modernity’s impact on Korean women’s psyche and social roles, and the progressive initiative of male teachers who advanced gender equality in new Korean religious movements. A range of data, including periodicals, letters, and newspaper articles, enable us to understand the changing face of women during the process of modernization in Korea. This paper gives voice to the significant role of Yi Ch’ŏngch’un, an exceptional financial sponsor in the formative years of Wŏn Buddhism and an advocate for women’s rights. By highlighting her contributions, it becomes clear that the progressive males who pushed for gender equality relied on the support of female-ordained devotees to actualize the doctrine’s ideal.